User Experience, Ease of Transactions, and Consumers Trust Towards Decisions Use of the Fund Application (Study of Dana Application Users in Central Jakarta) - Imelda Aprileny Leny; Afdhal Alifian; Jayanti Apri (Indonesia Banking School, 2024)
This study aims to find out how much user experience, ease of transactions and consumer trust influence on use decisions. This is a quantitative research with a descriptive approach. The population of this study is all Dana application users in Central Jakarta. The sample of this study is a random sample, where samples are taken from randomly with 50 respondents with criteria of residing in the Central Jakarta area and having used the Dana application for more than 3 months. The results of the study showed that the following variables: (1) User Experience had a positive effect on User Decision. (2) Ease of Transaction has a positive effect on the User's Decision. (3) Consumer trust has a positive effect on User Decisions. (4) User Experience, ease of transaction and consumer trust have a combined effect on the User's Decision.